Meta-analysis shows that mesenchymal stem cell therapy can be a possible treatment for diabetes - Habiba, Umm E.; Khan, Nasar; Greene, David Lawrence; Ahmad, Khalil; Shamim, Sabiha; Umer, Amna (Frontiers in Endocrinology, 2024)
Objective: This meta-analysis includes the systematic literature review and meta-analysis involving clinical trials to assess the efficacy and safety of MSCs transplantation for treating T1DM and T2DM. Methods: We searched PubMed, ScienceDirect, Web of Science, clinicaltrials.gov, and Cochrane Library for "published" research from their inception until November 2023. Two researchers independently reviewed the studies' inclusion and exclusion criteria. Our metaanalysis included 13 studies on MSC treatment for diabetes. Results: The MSC-treated group had a significantly lower HbA1c at the last follow-up compared to the baseline (MD: 0.95, 95% CI: 0.33 to 1.57, P-value: 0.003 < 0.05), their insulin requirement was significantly lower (MD: 0.19, 95% CI: 0.07 to 0.31, P-value: 0.002 < 0.05), the level of FBG with MSC-transplantation was significantly dropped compared to baseline (MD: 1.78, 95% CI: -1.02 to 4.58, P-value: 0.212), the FPG level of the MSC-treated group was significantly lower (MD: -0.77, 95% CI: -2.36 to 0.81, P-value: 0.339 > 0.05), and the fasting C-peptide level of the MSC-treated group was slightly high (MD: -0.02, 95% CI: -0.07 to 0.02, P-value: 0.231 > 0.05).The transplantation of MSCs has been found to positively impact both types of diabetes mellitus, without signs of apparent adverse effects.